(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article is devoted to the study of English idioms with flora component, their meaning and use in speech. The aim of the work is to define the concept of "idioms", the history of idioms with the component of flora, centuries-old human observations of the world of flora and the attitude of people to this area of reality. The article also reveals the peculiarities of English idioms with flora component important for translation and considers the problem of adequacy and equivalence in translation, as well as the ways of translation of English idioms into Uzbek. The present article is devoted to investigation of idioms with the component of the flora, their importance and use in speech. The aim of the work is to define the concept of "idiom". The history of occurrence of idioms with flora component is considered. Identify the features of idioms that are important for translation and methods of translation of English idiom with the component flora